Single‐cell profiling of T lymphocytes in deficiency of adenosine deaminase 2. Issue 2 (3rd November 2021) - Wu, Zhijie; Gao, Shouguo; Watanabe, Naoki; Batchu, Sai; Kajigaya, Sachiko; Diamond, Carrie; Alemu, Lemlem; Raffo, Diego Quinones; Feng, Xingmin; Hoffmann, Patrycja; Stone, Deborah; Ombrello, Amanda; et al.
Abstract: Deficiency of adenosine deaminase 2 (DADA2) is a monogenic vasculitis syndrome caused by autosomal‐recessive loss‐of‐function mutations in the ADA2 gene (previously known as CECR1 ). Vasculitis, vasculopathy, and inflammation are dominant clinical features of this disease; the spectrum of manifestations includes immunodeficiency and lymphoproliferation as well as hematologic manifestations. ADA2 is primarily secreted by stimulated monocytes and macrophages. Aberrant monocyte differentiation to macrophages and neutrophils are important in the pathogenesis of DADA2, but little is known about T lymphocytes in this disease. We performed combined single‐cell RNA sequencing and single‐cell TCR sequencing in order to profile T cell repertoires in 10 patients with DADA2. Although there were no significant alterations of T cell subsets, we observed activation of both CD8 + and CD4 + T cells. There was no clonal expansion of T cells: most TCRs were expressed at basal levels in patients and healthy donors. TCR usage was private to individual patients and not disease specific, indicating as unlikely a common pathogenic background or predisposition to a common pathogen. We recognized activation of IFN pathways as a signature of T cells and STAT1 as a hub gene in the gene network of T cell activation and cytotoxicity. Overall, T cells in DADA2 patients showed distinct cell–cell interactions with monocytes, as compared with healthy donors, and many of these ligand–receptor interactions likely drove up‐regulation of STAT1 in both T cells and other immune cells in patients. Our analysis reveals previously undercharacterized cell characteristics in DADA2. Graphical Abstract: T lymphocytes are activated and actively involved in DADA2 pathogenesis; and ligand‐receptor crosstalk with monocytes likely leads to up‐regulation of STAT1 and subsequently augmented responses of cells to IFN upon stimulation.